Direct observation of 3D nitrogen distribution in silicon-based dielectrics using atom probe tomography - Byeong-Gyu Chae; Jeong Yeon Won; Young Sik Shin; Dong Jin Yun; Jae min Ahn; Seon Tae Park; Ki-bum Lee; Hokyun An; Mina Seol; I-Jun Ro; Se-Ho Kim; Chunhyung Chung; et al. (Nature Communications)
Abstract The distribution of nitrogen in semiconductor devices plays a crucial role in tuning their physical and electrical properties. However, direct observation and precise quantification of nitrogen remain challenging because of analytical limitations, particularly at critical interfaces in silicon-based semiconductors. Although atom probe tomography has emerged as a powerful tool, distinguishing nitrogen from silicon without isotope doping is persistently difficult. In this study, we employ advanced atom probe tomography with an extended flight path under optimized conditions to characterize the three-dimensional nitrogen distribution in actual device structures, including 2- and 5-nm-thick silicon dioxide/silicon oxynitride-based gate dielectrics and a fin-structured three-dimensional device. Our analysis reveals that the nitrogen distribution determines the formation of the nitrogen profile in gate dielectrics, which in turn affects the diffusion of impurities, ultimately impacting the electrical properties and reliability. Our work provides insights into atomic-scale nitrogen behavior, paving the way for advancing next-generation semiconductor devices.